The effect of consumptions of anadara granosa on hematological parameters in rats / Nuursolihah Zainal Abidin - Zainal Abidin, Nuursolihah (2015)
Blood cockle is known to be rich in protein and iron compared to other seafood. Seafood generally has the ability to boost hematological parameters when consumed in appropriate amounts and time. This study was designed to determine the protein content of blood cockle and evaluate the effect of blood cockle extract to boost hematological parameter in rats. Eighteen rats were divided randomly into 3 groups: control (normal diet), low dose (7.0 mg/ml protein / kg) and high dose (52.0 mg/ml protein / kg). Both low and high dose groups were given the respective dose orally for 3 consecutive weeks. Lymphocyte and MCV values showed significant differences (p = 0.043, P = 0.043) respectively between control and high dose groups. There was a significant difference in WBC value between low dose and high dose groups (p = 0.049). Significant differences were also observed in Hb, HCT and RDW values between low dose and high dose groups (p = 0.042,p = 0.020,p = 0.019). Based on the findings, it can be concluded that blood cockle has high protein content and capabilities in boosting hematological parameters